Influence of biological inductors on the synthesis and biological activity of microbial metabolites - Pirog, Tatiana; Ivanov, Mykyta (My University, 2023)
The increasing antibiotic resistance is a severe concern for humanity. Co-cultivation of microorganisms is a promising method for obtaining new secondary antimicrobial metabolites. An effective strategy for co-cultivation of microorganisms involves the usage of certain biological inductors. The aim of this review is to summarize existing scientific research in the literature related to the influence of physiologically different types of biological inductors on the synthesis and biological activity of microbial secondary metabolites. An analysis of the literature has shown that in such studies, either live or inactivated cells of the inductor are added to the culture medium at significantly lower concentrations compared to the producer cells of the final metabolites, or the supernatant (filtrate) after cultivation of a competitive microorganism is used as an inductor. According to the literature and our own experimental studies, the using inductors is an effective approach not only for intensifying the synthesis of bacteriocins, surfactants, and antibiotics, but also for increasing their biological activity. Additionally, it often leads to the production of novel antimicrobial compounds that are not typical for the producer. However, the mechanisms of effect of inductors on the synthesis of biologically active secondary metabolites require further research, as the literature suggests that their introduction into the cultivation medium of producer does not always lead to an intensification of the synthesis of the final product. Moreover, the biological activity of secondary metabolites depends on the cultivation conditions of the producer, including the presence of biological inductors in the culture medium. Therefore, it is essential to conduct further research on the interaction between producers and competitive microorganisms to regulate the biological activity of the synthesised metabolites. In addition, there is a necessity to search for more cost-effective substrates for the biosynthesis of secondary metabolites, optimize the composition of the culture medium and expand the range of both pro- and eukaryotic inductors

Зростаюча стійкість до антибіотиків викликає серйозне занепокоєння у людства. Кокультивування мікроорганізмів є перспективним методом отримання нових вторинних антимікробних метаболітів. Ефективна стратегія спільного культивування мікроорганізмів передбачає використання певних біологічних індукторів. Метою цього огляду є узагальнення наявних у літературі наукових досліджень щодо впливу фізіологічно різних типів біологічних індукторів на синтез і біологічну активність мікробних вторинних метаболітів. Аналіз літератури показав, що в таких дослідженнях живі або інактивовані клітини індуктора додають до культурального середовища у значно нижчих концентраціях порівняно з клітинами-продуцентами кінцевих метаболітів або супернатант (фільтрат) після культивування як індуктор використовується конкурентний мікроорганізм. За даними літератури та власних експериментальних досліджень, використання індукторів є ефективним підходом не лише для інтенсифікації синтезу бактеріоцинів, поверхнево-активних речовин та антибіотиків, а й для підвищення їх біологічної активності. Крім того, це часто призводить до виробництва нових антимікробних сполук, нетипових для виробника. Проте механізми впливу індукторів на синтез біологічно активних вторинних метаболітів потребують подальших досліджень, оскільки в літературі стверджується, що введення їх у середовище культивування продуцента не завжди призводить до інтенсифікації синтезу кінцевого продукту. Крім того, біологічна активність вторинних метаболітів залежить від умов культивування продуцента, в тому числі від наявності біологічних індукторів у культуральному середовищі. Тому вкрай необхідно проводити подальші дослідження взаємодії продуцентів і конкурентних мікроорганізмів для регуляції біологічної активності синтезованих метаболітів. Крім того, існує необхідність пошуку більш економічно ефективних субстратів для біосинтезу вторинних метаболітів, оптимізації складу живильного середовища та розширення спектру як про-, так і еукаріотичних індукторів
Keywords: культивування; індуктор; біосинтез; вторинні метаболіти; co-culture; inductor; biosynthesis; secondary metabolites; кафедра біотехнології і мікробіології